Life history traits of the snapping shrimp alpheus carlae (Decapoda: Alpheidae) from the south-eastern coast of Brazil - Ghizelli-Fraga, Bianca [UNESP]; Costa, Rogerio C. [UNESP]; Pescinelli, Régis A. [UNESP] (My University, 2021)
The life history traits of the snapping shrimp Alpheus carlae were investigated. We evaluated the relative growth, morphological sexual maturity, sexual dimorphism, handedness, fecundity, and egg volume. Sampling was performed monthly in an estuarine region of Cananéia, in the south-eastern coast of Brazil. The following structures were measured to perform the relative growth analysis: length of carapace and second pleonal pleuron, length, width and height of major cheliped propodus, and length of appendix interna and appendix masculina. Juveniles and adults males and females have different growth patterns, indicating distinct strategies of energy allocation. The estimated carapace length at the onset of morphological sexual maturity of females and males was 5.6 mm and 6.2 mm, respectively. The sexual dimorphism of specific body structures was evident, mainly in the appendix interna of females and major cheliped of males. There was no evidence of handedness in females or males. The mean fecundity of females was 364 ± 204 eggs (mean ± SD) eggs and was positively correlated with the carapace length. The egg volume differed between developmental stages I and II, and I and III, with an overall volume increase of 73.23% and 95.45%, respectively. The results contribute to the knowledge about A. carlae and its life history in natural environment.
Keywords: Caridea; Egg production; Relative growth; Sexual dimorphism